Onset and resolution of pain among treated and untreated posterior teeth with a visible crack: Three-year findings from the national dental practice-based research network. (April 2022) - Funkhouser, Ellen; Ferracane, Jack L.; Hilton, Thomas J.; Gordan, Valeria V.; Gilbert, Gregg H.; Mungia, Rahma; Burton, Vanessa; Meyerowitz, Cyril; Kopycka-Kedzierawski, Dorota T.; ,
Abstract: Objective: Cracked teeth may be associated with pain, especially biting pain, and to a lesser degree cold and spontaneous pain.  Described are how commonly these pains remain constant, develop, or resolve over time, none of which have been well-described, especially among untreated cracked teeth. Methods: Cracked teeth from the Cracked Tooth Registry (CTR) study were followed for 3 years.  Assessments of cold, biting, and spontaneous pain and treatments performed were completed at enrollment (Y0) and at each annual recall visit. Results: 209 practitioners enrolled 2, 858 patients, each with a visible crack on a posterior tooth; 2601 (91%) patients attended at least one recall visit. Overall, 960 (37%) were treated, primarily with crowns. Among both treated and untreated cracked teeth with biting pain or spontaneous pain at Y0, the vast majority (92–99%) had their pain resolved by the time of a recall visit and 85–93% remained pain-free after initial resolution. The observations for cold pain were similar: 68% (untreated) and 78% (treated) became free of cold pain at some point during follow-up, and 84% of these stayed free of cold pain after initial resolution. Few teeth developed biting or spontaneous pain (4–8%) and 44–67% of these had pain resolution during the follow-up period. Conclusion: In this study, treatment resolved a preponderance of pain associated with a cracked tooth.  Pain was also resolved for most untreated cracked teeth, especially biting pain, and to a lesser degree spontaneous and cold pain, although not to the same degree as with the treated cracked teeth.